Economy and society : a study in the integration of economic and social theory - Parsons, Talcott, 1902-1979 (International library of sociology., 1956)
This volume is designed as a contribution to the synthesis of theory in economics and sociology. We believe that the degree of separation between these two disciplines separation emphasized by intellectual traditions and present institutional arrangements arbitrarily concealsa degree of intrinsic intimacy between them which must be brought to the attention of the respective professional groups.